2017
DOI: 10.5688/ajpe6100
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of an Elective on the Ethnopharmacology of Appalachia for the PharmD Curriculum

Abstract: Objective. To create and implement a class in ethnopharmacology that would educate student pharmacists on folk medicine, including home remedies and native plants that are used as alternative medicinal sources; active components of medicinal plants including toxicity issues and the mechanism of action of beneficial compounds, such as catechins and other flavonoids; and nutraceuticals and poisonous plants. Methods. In this three-credit hour class, herbal remedies are investigated from the standpoints of medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 9 publications
(8 reference statements)
0
7
0
1
Order By: Relevance
“…Examples of metrics that were used to study the academic performance were average final course scores, 20,[25][26][27] a range of final course scores, 28,29 , average student scores on various course assessments such as examinations, 20-22, 24-26, 30, 31 quizzes, 20,23,32,33 or other assignments. 20,26,27,33,34 In a few cases where the course intervention was limited to a certain part of the course the metric used to assess academic performance was not the entire assessment but the score on a group of questions that were related to the intervention. 19,23,30 Final course letter grades 20,21,25 and the number or percentage of students who passed or failed examinations 21,22,31 were also used as metrics for academic performance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Examples of metrics that were used to study the academic performance were average final course scores, 20,[25][26][27] a range of final course scores, 28,29 , average student scores on various course assessments such as examinations, 20-22, 24-26, 30, 31 quizzes, 20,23,32,33 or other assignments. 20,26,27,33,34 In a few cases where the course intervention was limited to a certain part of the course the metric used to assess academic performance was not the entire assessment but the score on a group of questions that were related to the intervention. 19,23,30 Final course letter grades 20,21,25 and the number or percentage of students who passed or failed examinations 21,22,31 were also used as metrics for academic performance.…”
Section: Resultsmentioning
confidence: 99%
“…The three major approaches in the description of student evaluations were to generally describe the evaluations as a whole or in part; 15,22,24,30,36 to present evaluation scores; and/or to delineate the students' written comments. In the presentation of evaluation scores, various studies provided different metrics, such as one score that averaged all items regarding the instructor 20,21 or the course; 20,26,32 average scores for different items regarding the course 24,28,29,32 or both the course and the instructor; 25,36,49 or average scores for one item regarding the course. 15,30 In the presentation of student comments the main approaches were to provide a summary of the comments, 20-22, 24, 26, 30 excerpts from the comments, 25,26,28,29,44 or both.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cursos e apresentações educativas são essenciais para preparar os alunos para aconselhamento adequado, enfatizando também a sensibilidade cultural dos farmacêuticos. Estes profissionais desempenham um papel essencial na orientação segura do uso de plantas medicinais (Linger, 2017).…”
Section: A Importância Do Farmacêutico Na Orientação Do Uso Seguro E ...unclassified
“…Unfortunately, society's recognition of medicinal plants differs from that of the current millennial generation. The results of studies (Harfouche et al, 2021;Linger, 2017;Ojalehto et al, 2017;Templeman et al, 2018) have found that students have been skeptical or doubtful of belief claims related to the utilization of medicinal plants as traditional medicine. Students' skepticism about the benefits of medicinal plants may have been due to the lack of evidential support (Ojalehto et al, 2017), differences with modern medical approaches (Linger, 2017), cultural influences and myths (Templeman et al, 2018), safety and risk (Harfouche et al, 2021), and negative experiences or Abstract.…”
Section: Introductionmentioning
confidence: 99%